(untitled) (Biological Sciences - PJSIR, 2009)
In the study of the effect of zinc (Zn) on root nodule stimulation and yield of chickpea under the climatic condition of D.I. Khan, Pakistan, significant effect of application of varying levels of zinc was noted. Plant height was significantly more as compared to the control. The plants receiving 7.5 kg/ha Zn had the highest weight of nodules/plant and produced maximum grain yield of 1185 kg/ha.